1998
DOI: 10.1148/radiology.206.1.9423656
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous lung attenuation at thin-section CT: diagnostic value of expiratory scans.

Abstract: Expiratory scans significantly improved diagnostic accuracy in patients with inhomogeneous attenuation on inspiratory scans, and they helped in the diagnosis of diffuse lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(49 citation statements)
references
References 0 publications
1
46
0
2
Order By: Relevance
“…It is recognized during the expiratory phase as reduced attenuation of the lung parenchyma, especially apparent as lowerthan-usual density ( Figure 1) and absence of volume reduction. (8)(9)(10) See also Mosaic attenuation/perfusion pattern.…”
Section: Glossary 1 Air Trapping (Aprisionamento Aéreo)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized during the expiratory phase as reduced attenuation of the lung parenchyma, especially apparent as lowerthan-usual density ( Figure 1) and absence of volume reduction. (8)(9)(10) See also Mosaic attenuation/perfusion pattern.…”
Section: Glossary 1 Air Trapping (Aprisionamento Aéreo)mentioning
confidence: 99%
“…(62,63) Air trapping secondary to bronchial or bronchiolar obstruction can produce parenchymal foci of lower attenuation, which become more evident in expiratory CT scans. (8) In obliterative small-airways disease and vascular occlusive disease, the areas of low attenuation are abnormal; in general, the number and size of pulmonary vessels in these areas are reduced when compared with those in the adjacent normal lung, which might present normal or increased attenuation (due to redirec-…”
Section: Ground-glass Opacity/attenuation (Opacidade/atenuação Em Vidmentioning
confidence: 99%
“…This important sign of enhancement of the mosaic attenuation pattern on CT sections obtained at endexpiration (usually limited to approximately six sections taken between the aortic arch and right hemidiaphragm) has led some workers to suggest that they should be acquired routinely, irrespective of the findings on the standard inspiratory HRCT sections [15,16]. Whether expiratory CT sections need to be obtained in all cases of suspected small airways disease is questionable.…”
Section: High-resolution Computed Tomographic Techniquementioning
confidence: 99%
“…The crosssectional area of the affected parts of the lung do not decrease in size on expiratory CT [91]. Expiratory CT may also be helpful in differentiating between the three main causes of a mosaic pattern (infiltrative lung disease, small airways disease, and occlusive pulmonary vascular disease) which may be problematic on inspiratory CT [15,94]. An important caveat is that in patients with widespread small airways disease, endexpiratory CT sections may appear virtually identical to the standard inspiratory CT sections, simply because of the severity of the air-trapping (i.e.…”
Section: Air-trapping At Expiratory Computed Tomographymentioning
confidence: 99%
“…They found it uniform everywhere at TLC, but there was a vertical gradient of alveolar volume at FRC. Because the tissue density of lung parenchyma is reciprocal to the alveolar volume, their findings indicated that the tissue density is uniform at TLC and gravity-dependent at FRC, which today we can see by inspiratory and expiratory chest CT images [14]. The uniform density at TLC is thought to result from the respiratory muscle power that generates uniform intrathoracic pressure against gravity.…”
mentioning
confidence: 97%